INFORMATION TOOLS: OPPORTUNITIES OF BI PLATFORM TO EVALUATE EDUCATION QUALITY - Saydulaev, Deni; Vysotskaya, Nataliya; Kochetkov, Evgeniy (Revista Inclusiones, 2020)
This work is aimed at determination of opportunities of BI platforms as a tool of quality evaluation of higher education. Main results. This article determines the trends of application of BI platform as an information tool to evaluate education quality. It has been established that BI provides uniformity of metadata for all tools and unified user-friendly methods of searching, acquisition, saving, reusing, and publication of metadata objects. OLAP enables end users to analyze data by means of rapid requests and predictions, whereas the simulation and Data Mining allow to classify and to rank information on the basis of regulations. As exemplified by separate BI platforms, the BI opportunities are analyzed, as well as comparative criteria of various platforms, and the trends are revealed to use BI platform as information system of decision making for managers in educational sphere.